Specifics of business processes of petrochemical enterprises in the context of digitalization of the economy - E. A. Dolonina; M. V. Shinkevich (Вестник университета)
Digital transformation is more focused on the management aspects of digitalization. It is associated with a large-scale process of implementing digital technologies and corresponding organizational changes. The article reveals the features of designing business processes of petrochemical enterprises in the context of the transition to the digital economy and the introduction of new technologies in the production process. The paper identifies the main technologies of Industry 4.0 used in the chemical and petrochemical industries. The study analyses the key technologies and drivers of the development of traditional and digital production, as well as the barriers to their implementation. The author summarizes the key principles on which Industry 4.0 should be based in order to support effective decision-making in the industry. The paper notes that the design of business processes is determined by the production technology. In the direction of improving business processes, there is a need for wider use of decision support systems based on artificial intelligence and expert systems. The authors developed a model for the implementation of production processes that takes into account the design features of business processes of industrial enterprises in the conditions of digitalization of the economy. The distinctive feature of the presented model is the combination of the life cycle and the value stream with a structured approach to defining the components of Industry 4.0.